Cerebellar involvement in Parkinson's disease resting tremor. Issue 1 (December 2016) - Lefaivre, Shannon; Brown, Matt; Almeida, Quincy
Abstract Background There exists a lack of consensus regarding how cerebellar over-activity might influence tremor in Parkinson's disease (PD). Specifically, it is unclear whether resting or postural tremor are differentially affected by cerebellar dysfunction. It is important to note that previous studies have only evaluated the influence of inhibitory stimulation on the lateral cerebellum, and have not considered the medial cerebellum. The aim of the current study was to compare the effects of a low-frequency rTMS protocol applied to the medial versus lateral cerebellum to localize the effects of cerebellar over-activity. Methods Fifty PD participants were randomly assigned to receive stimulation over the medial cerebellum (n = 20), lateral cerebellum (n = 20) or sham stimulation (n = 10). 900 pulses were delivered at 1Hz at 120 % resting motor threshold of the first dorsal interosseous muscle. Tremor was assessed quantitatively (before and after stimulation) using the Kinesia Homeview system which utilizes a wireless finger accelerometer to record tremor. Results The main finding was that resting tremor severity was reduced in tremor-dominant individuals, regardless of whether stimulation was applied over the medial (p = 0.024) or lateral (p = 0.033) cerebellum, but not in the sham group. Conclusion Given that the cerebellum is overactive in PD, the improvements in resting tremor following an inhibitory stimulation protocol suggest that over-activity in cerebellar nuclei may be involved in the generation of resting tremor in PD. Low-frequency rTMS over the medial or lateral cerebellum provides promise of an alternative treatment for tremor in PD, a symptom that is poorly responsive to dopaminergic replacement.